IMPLEMENTATION OF HEALTHCARE SERVICES FOR VULNERABLE AND HIGH-RISK INMATES AT CLASS IIA CORRECTIONAL FACILITY IN KARAWANG - Dayana, Nina; Jarodi, Odi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to evaluate the implementation of health services in Class IIA Karawang Prison, specifically for vulnerable and high-risk inmates. Health services within the prison include promotive, preventive, curative, and rehabilitative aspects; however, their implementation has not been optimal due to limitations in facilities and medical personnel. The overcapacity situation at Karawang Prison further increases the risk of infectious and chronic diseases among inmates, necessitating greater attention to fulfilling their health rights. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation, involving vulnerable inmates, inmates with high-risk health conditions, and medical staff. The results indicate the need for improved health facilities, an increase in medical personnel, and enhanced quality of health services to ensure that inmates' health rights are met optimally according to applicable regulations. Keywords: Health Services; Service Quality; High Risk